PENGARUH PENDIDIKAN GIZI SEIMBANG TERHADAP PENINGKATAN PENGETAHUAN DAN POLA MAKAN REMAJA SMP NEGERI 1 ARONGAN LAMBALEK - Khairatul Diani, Ria; Khairunnas (Jurnal Biogenerasi, 2025)
One of the causes of nutritional problems among adolescents was the lack of knowledge about nutrition and irregular eating patterns, which became one of the factors leading to an imbalance in nutrient intake. Nutritional imbalances during adolescence could result in various negative impacts such as anemia, obesity, growth disorders, and decreased concentration in learning. This study aimed to analyze the effect of Balanced Nutrition Education on improving knowledge and eating patterns among students at SMP Negeri 1 Arongan Lambalek. The method used was a quantitative approach with a one-group pre-test and post-test design. The analysis employed the Wilcoxon test. The results showed that there was a significant effect of Balanced Nutrition Education on improving adolescents' knowledge at SMP Negeri 1 Arongan Lambalek (p-value = 0.000 < 0.05), and there was a significant effect on adolescents' eating patterns (p-value = 0.008 < 0.05). Conclusion there was an effect of Balanced Nutrition Education on increasing knowledge and improving eating patterns among students at SMP Negeri 1 Arongan Lambalek. Recommendation future research was advised to include other variables such as attitudes, balanced nutrition practices, and to extend the duration of nutritional interventions for more detailed results.